2022
DOI: 10.1038/s41598-022-20916-y
|View full text |Cite
|
Sign up to set email alerts
|

Utility of standard diffusion-weighted magnetic resonance imaging for the identification of ischemic optic neuropathy in giant cell arteritis

Abstract: This study assessed diffusion abnormalities of the optic nerve (ON) in giant cell arteritis (GCA) patients with acute onset of visual impairment (VI) using diffusion-weighted magnetic resonance imaging (DWI). DWI scans of GCA patients with acute VI were evaluated in a case-control study. Two blinded neuroradiologists assessed randomized DWI scans of GCA and controls for ON restricted diffusion. Statistical quality criteria and inter-rater reliability (IRR) were calculated. DWI findings were compared to ophthal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…In 2021, Kaur et al performed an experiment to monitor ocular pressure changes during prone spine surgery and found that ocular pressure was significantly elevated at the end of the case when compared to baseline pressures [64]. Danyel et al described the use of diffusion-weighted MRI to diagnose ION in patients with giant cell arteritis [65].…”
Section: -Presentmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2021, Kaur et al performed an experiment to monitor ocular pressure changes during prone spine surgery and found that ocular pressure was significantly elevated at the end of the case when compared to baseline pressures [64]. Danyel et al described the use of diffusion-weighted MRI to diagnose ION in patients with giant cell arteritis [65].…”
Section: -Presentmentioning
confidence: 99%
“…The presentation of PION will be consistent with optic neuropathy, but with an unremarkable fundoscopic exam [36]. While PION is often a diagnosis of exclusion, recent reports have argued for the use of diffusion weighted imaging (DWI) to diagnose the acute phase of PION [55,61,65]. DWI has been applied to AION and shows promise in detecting ischemic changes [81].…”
Section: Assessment and Diagnosismentioning
confidence: 99%
See 1 more Smart Citation
“…In 2019, Matsuoka et al reported, to our knowledge, the first case with an abnormal DWI signal of the temporal arteries (TAs) [10]. Recently, a few additional cases of DWI in GCA were published [11][12][13]. DWI is based on the measurement of random Brownian motion of water molecules.…”
Section: Introductionmentioning
confidence: 99%